Kesadaran Masyarakat dalam Memberdayakan BMT (Baitul Mall Wattam will) Serambi Madinah Kabupaten Kerinci - Alek Wissalam Bustami; Helfenta Helfenta (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to find, (1) how the level of awareness in empowering society BMT for the welfare of the BMT Serambi Madinah Kerinci. (2). To find out how the performance BMT Porch Medina in achieving the common goal of BMT developments foyer and for the community. (3). To determine the factors causing the lack of public awareness of the BMT Serambi Madniah Kerinci. This study employed a descriptive qualitative approach and used data collection methods through observations, interviews, and documentation. By using comprehensive model analysis, namely domain analysis, taxonomy analysis, compositional analysis and cultural issue analysis. This study also used multiple models to validate the data triangulation to further refine this study. This study found, 1). One factor in the lack of public awareness in civilizing BMT is in spite of public awareness is relatively low both in terms of the management of the BMT and the system of sharia run by BMT itself, is also a lack of socialization between the BMT citizens regarding BMT nowadays still in the development of the quality of BMT. (2). available lack of information by the public against the BMT Serambi Madinah and its Lack of public knowledge about the system and mamfaat BMT for society into something that must be improved. Since society and the BMT should be a good cooperation in order to achieve the common goal of advancing the local economy. (3). BMT Serambi Madinah performance systems to improve public knowledge of the BMT in terms of empowering BMT for welfare, are still at the development stage and institutions still lack the BMT to community relations. This resulted in a lack of public awareness to BMT Serambi Madinah resulting lack of positive response from the community so as not achieving common goals in terms of improving the welfare of the community, especially medium. In the results of this study showed that, (1). the community has the same complaint against the BMT that a lack of people get information about BMT. (2). Medina Porch performance BMT managers today have not fully succeeded in its achievements. Because there are among of managers who do not work optimally in its function, resulting in inhibition of the progress of the foyer BMT Medina. (3). motivating factors to do the BMT in enhancing co-operation with the community is to be a good relationship between the BMT with the community either in the form of promotion or dissemination.